Analisis Model Regresi Linear Berganda dengan Metode Response Surface - Murti, Henoh Bayu (GRADIEN : Jurnal Ilmiah MIPA, 2014)
Problem in analysis of regression research is the need of more than one independent variables in regression model. This condition often causes complication in estimating an important response, which results multiple linear regression that is not optimal.Â  In this condition, it is needed an optimalization that is essential in multiple linear regression. To be able to use independent variables optimally, response surface method is used. This method determines approaching function that is suitable in estimating the next dependent variable y. Optimal point of the result of the optimalization of multiple linear regression using three independent variables of the data of reaction rate for catalytic isomerization of n-pentane to isopentane is on saddle point.